2022
DOI: 10.25304/rlt.v30.2802
|View full text |Cite
|
Sign up to set email alerts
|

The impact of online learning technology on self-regulation and student success

Abstract: The research purpose is to analyse the self-regulation of students who use the massive open online course (MOOC) technology to learn the exact sciences. The sample included 252 students: females were 47%, and males were 53%. The average age of students was 20.08 ± 0.72. The students were divided into two groups: group 1 consisted of students who learnt the Digital singular (nano) optics course online using the MicrosoftTeams platform with teacher’s support; group 2 consisted of students who learnt the MOOC cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…This can help individuals make better and more informed career decisions (Hsu et al, 2021). Technology can be used in the implementation of counseling to create an interactive learning environment and increase learning effectiveness (Makhno et al, 2022). The use of technology in learning has become synonymous with 21st century learning and has encouraged the development of more varied and innovative learning models (Sarwendah et al, 2023).…”
Section: Mindfulness Techniques Into Group Counseling As a Technique ...mentioning
confidence: 99%
See 1 more Smart Citation
“…This can help individuals make better and more informed career decisions (Hsu et al, 2021). Technology can be used in the implementation of counseling to create an interactive learning environment and increase learning effectiveness (Makhno et al, 2022). The use of technology in learning has become synonymous with 21st century learning and has encouraged the development of more varied and innovative learning models (Sarwendah et al, 2023).…”
Section: Mindfulness Techniques Into Group Counseling As a Technique ...mentioning
confidence: 99%
“…Quality of Counseling in the Use of Technology (Lau et al, 2019), (Edwin et al, 2022), (Margevica-Grinberga & Smitiņa, 2021), (Makhno et al, 2022), (Ifenthaler & Egloffstein, 2019) Technology can help counselors build stronger relationships with students. Counselors can use technology to connect with students one-on-one and to provide ongoing support.…”
mentioning
confidence: 99%
“…Some of the MOOC attributes that highlight the feature of interactivity includes real-time and rich communication with quality video presentations and the inclusion of hypermedia didactic materials to enhance the effectiveness of interactions between instructors and learners. Makhno et al (2022) suggested that use of interactive elements in MOOCs promotes active learning and creation of learning environments that promoted metacognition, self-regulation and personalized learning. Thomas and Alkhafaji (2023) conducted an empirical study to investigate the learner perceptions towards the AI supported chatbots in the context of MOOCs and identified that learners found it enjoyable and comfortable to engage with chatbot-supported communication channels and felt it as an efficient means towards quick access and retrieval of information.…”
Section: Interactivity In Moocsmentioning
confidence: 99%